2019
DOI: 10.1007/s11523-019-00632-w
|View full text |Cite
|
Sign up to set email alerts
|

Toxicities with Immune Checkpoint Inhibitors: Emerging Priorities From Disproportionality Analysis of the FDA Adverse Event Reporting System

Abstract: Background Different immune-related adverse events (irAEs) were described with immune checkpoint inhibitors (ICIs), including blockers of cytotoxic T-lymphocyte associated protein 4 (CTLA4) and programmed cell death 1 or its ligand (PD1/PDL1), although their global safety is incompletely characterized.Objective To characterize spectrum, frequency and clinical features of ICI-related adverse events (AEs) reported to the FDA Adverse Event Reporting System (FAERS). Patients and MethodsAEs from FAERS (up to June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 64 publications
3
65
0
Order By: Relevance
“…Overall, our data (a) confirmed the variegate pattern of cutaneous toxicity , including nonspecific manifestations such as rash maculopapular and pruritus, as well as serious irAEs and SCARs, thus making a timely consultation with dermatologist pivotal to minimize unnecessary drug interruption ; (b) found a differential reporting between anti‐PD1/PDL1 drugs (psoriasis, dermatitis psoriasiform, pemphigoid, and cutaneous sarcoidosis) and anti‐CTLA4 medications (acute febrile neutrophilic dermatosis and erythema nodosum) ; and (c) recorded a high proportion of death in young adults with SCARs, especially TEN (83% in adults aged 40–49), with a delayed latency as compared with recently published data on anticancer drugs (mean 46 vs. 18 days ), in keeping with immune‐related basis. This conflicts with the algorithm of drug causality for epidermal necrolysis (ALDEN), which was validated on heterogeneous drugs and suggested that late events are unlikely to be drug related ): we invite clinicians to submit complete high‐quality reports, as recommended by the Side Effect Reporting in Immuno‐Oncology (SERIO) working group .…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Overall, our data (a) confirmed the variegate pattern of cutaneous toxicity , including nonspecific manifestations such as rash maculopapular and pruritus, as well as serious irAEs and SCARs, thus making a timely consultation with dermatologist pivotal to minimize unnecessary drug interruption ; (b) found a differential reporting between anti‐PD1/PDL1 drugs (psoriasis, dermatitis psoriasiform, pemphigoid, and cutaneous sarcoidosis) and anti‐CTLA4 medications (acute febrile neutrophilic dermatosis and erythema nodosum) ; and (c) recorded a high proportion of death in young adults with SCARs, especially TEN (83% in adults aged 40–49), with a delayed latency as compared with recently published data on anticancer drugs (mean 46 vs. 18 days ), in keeping with immune‐related basis. This conflicts with the algorithm of drug causality for epidermal necrolysis (ALDEN), which was validated on heterogeneous drugs and suggested that late events are unlikely to be drug related ): we invite clinicians to submit complete high‐quality reports, as recommended by the Side Effect Reporting in Immuno‐Oncology (SERIO) working group .…”
Section: Resultssupporting
confidence: 75%
“…FAERS also allows to perform disproportionality analysis, a validated concept in pharmacovigilance, to assess whether suspected drug‐induced events are differentially reported with ICIs . In this study, we carried out the so‐called disproportionality analysis by therapeutic area, (i.e., we selected reports where at least one anticancer agent was recorded, as a proxy of neoplasia).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The case of oncology, and in particular immunotherapy, is not an exception, and a plethora of postmarketing DAs have documented the occurrence of various toxicities with ICIs in the real world [16,17]. Therefore, clinicians may wonder whether and how these data will impact their routine practice, especially in the era of real-world evidence and relevant debate on their complementary role with randomized controlled trials (RCTs).…”
Section: Introductionmentioning
confidence: 99%
“…Post-marketing monitoring is therefore crucial to timely characterize ILD and to target preventive strategies for diagnosis and management [ 8 ]. In this context, international spontaneous reporting systems, through collection of millions of worldwide reports, represent a primary source of data for safety assessment of recently marketed drugs receiving fast track designation and priority review, which deserve rigorous post-marketing monitoring [ 9 , 10 ]. In particular, the FDA Adverse Event Reporting System (FAERS) is the largest publicly available pharmacovigilance database particularly suitable to detect rare adverse events, which may escape detection and/or reporting from randomized controlled trials.…”
Section: Introductionmentioning
confidence: 99%